Pengaruh Akuntabilitas Pengelolaan Keuangan Alokasi Dana Desa, Kebijakan Desa Dan Kelembagaan Desa Terhadap Kesejahteraan Masyarakat Desa Kaera Kecamatan Pantar Timur Kabupaten Alor - Omar Dision Tuaty (Jurnal Ilmiah Wahana Pendidikan, 2023)
Welfare according to language is safe, secure and prosperous, so that welfare includes security, safety and prosperity. In general terms, prosperity refers to a state of well-being, a human condition in which people are prosperous, in good health and at peace. According to Soetomo, the level of community welfare contains three indicators, namely: Social Justice, Economic Justice and Democratic Justice. Social Justice, namely justice that is evenly distributed to all people which includes: education, electricity and water. This study aims to determine the Effect of Financial Management Accountability Allocation of Village Funds, Village Policies and Village Institutions on Community Welfare in Kaera Village, Pantar Timur District, Alor District, both partially and simultaneously. Respondents of this study amounted to 76 people. This type of research is field research and is quantitative, using a questionnaire as a data collection instrument. The data was then analyzed using the t-test to determine the partial effect and the F-test to determine the simultaneous effect on people's welfare with the results of the study as follows: 1. Financial management accountability variable for village fund allocation, village policies, village institutions and community welfare has a Pearson product moment correlation value above the limit of 0.3 for the validity test. 2. The financial management accountability variable for village fund allocation, village policies, village institutions and community welfare has a Cronbach alpha value above the limit of 0.6 for the reliability test. 3. The financial management accountability variable for village fund allocation, village policies, village institutions and community welfare has a test value for each classic assumption test that is above alpha and passes the classic assumption test. 4. There is no effect of Financial Management Accountability Allocation of Village Funds partially does not affect Community Welfare as evidenced by the sig t test value of 0.623, which is greater than the research alpha value of 5% (0.05). 5. There is an influence of Village Policy on Community Welfare, as evidenced by the sig t test value of 0.013, which is smaller than the research alpha value of 5% (0.05). 6. There is an influence of Village Institutions on Community Welfare, as evidenced by the sig t test value of 0.019, which is smaller than the research alpha value of 5% (0.05). 7. There is an influence of Financial Management Accountability Allocation of Village Funds, Village Policies and Village Institutions on Community Welfare as evidenced by the sig F test value of 0.016 which is smaller than the research alpha value of 5% (0.05). From the results of the research and the conclusions of the research, the research team suggested to the village government respondents that in the future they should embrace the village community more and expand the opportunities for the community to convey their aspirations, besides that the village government also needs to implement policies that are beneficial to the village community. On the other hand, the research team also suggested that respondents from the Kaera Village community, Pantar Timur District, Alor Regency, should participate in realizing society by creating a law-abiding, tolerant, just society and providing participation in providing advice to improve the welfare of the general public in the village.